The Use of Selective Hemoperfusion in Treatment of Toxic Rhabdomyolysis Complicated by Acute Kidney Injury - S. V. Masolitin; D. N. Protsenko; I. N. Tyurin; O. A. Mamontova; M. A. Magomedov; T. G. Kim; A. V. Yaralyan (Вестник анестезиологии и реаниматологии, 2022)
The objective: to improve treatment results in patients with toxic rhabdomyolysis (RM) complicated by acute kidney injury (AKI) through using selective hemoperfusion (НР).Subjects and Methods. The study included 45 patients aged 18 to 55 years diagnosed with toxic RM complicated by AKI. The patients were divided into two groups. Group 1 received standard conservative therapy. In Group 2, during the first day of treatment, HP was used to prevent AKI progression. Changes in clinical and laboratory parameters of RM and renal damage as well as treatment outcomes between the groups were analyzed and compared.Results. Significantly better decrease in myoglobin blood level was revealed in Group 2 from day 1 to day 7 of treatment. In Groups 1 and 2, these parameters made 26.3% and 52.1%, respectively. The use of НР allowed reducing the urine concentration of KIM-1 by day 3 of treatment in Group 2 by 16.9%, in Group 1, the urine concentration of KIM-1 increased by 15.5%. The frequency of RRT initiation for urgent indications decreased from 75% to 52.9% when using HP, as a result, duration of inpatient treatment decreased from 19.5 (14; 22) to 16.5 (13; 19) days, as well as the period of ICU stay from 11 (9; 15) to 8 (6; 11) days.Conclusions. The early use of НР as part of the complex intensive therapy of toxic RM complicated by the development of AKI is accompanied by an earlier and significant decrease in laboratory markers of RM and AKI compared to standard treatment, as well as shorter ICU and hospital stay